THE EFFECT OF THE IMPLEMENTATION OF CARBON ACCOUNTING, DEBT TO EQUITY RATIO AND DIVIDEND PAYOUT TO RATIO ON COMPANY VALUE WITH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE PERFORMANCE AS MEDIATING VARIABLES IN PALM OIL PLANTATION COMPANIES ON THE INDONESIA ST - Ismi Izzati; Keulana Erwin; Isfenti Sadalia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of Carbon Accounting, Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) on Firm Value with Environmental, Social, and Governance (ESG) as a mediating variable. The research focuses on palm oil plantation subsector companies that have met sustainability criteria according to the OJK Green Taxonomy. These criteria include the publication of sustainability reports consecutively during 2020–2024, the implementation of carbon accounting, ownership of ISPO and RSPO certification, and having an ESG score from global rating agencies such as Sustainalytics, SPOTT, or CSRHub. The sample used consists of five large companies selected through a purposive sampling method, with consideration of compliance with predetermined technical criteria. The analytical methods used in this study were panel data regression and path analysis to examine the direct and indirect relationships between variables. The results showed that carbon accounting has a positive and significant effect on firm value, indicating that companies that are more transparent in reporting their emissions tend to be more valued by the market. DPR also has a positive and significant effect on firm value, while DER has a negative but insignificant effect. In the mediation model, ESG is proven to significantly mediate the relationship between carbon accounting and firm value, but does not mediate the influence of DER and DPR.These findings underscore the importance of integrating sustainability aspects into corporate strategy, not only to comply with regulations but also to add value to the company. ESG and carbon accounting have proven to be not only indicators of compliance but also capable of strengthening a company's financial value.